The influence of audit committee characteristics on impression management in chairman statement: Evidence from Malaysia - Yahya Mohammed Al-Sayani; Mohamad Naimi Mohamad Nor; Noor Afza Amran (Cogent Business & Management, 2020)
After the emergence of financial scams like Enron, WorldCom and Toshiba, the researchers have emphasized the significance of the audit committee (AC) in curtailing the earnings management (EM). The role of the AC in financial reporting has received significant attention in accounting research because it offers information to shareholders for investment decision making. Researchers have examined whether AC characteristics mitigate managers' EM practices. Whereas there is a scarcity of research that investigates the association among ACs and impression management (IM). The objective of this research is to examine the relationship between the AC characteristics and IM practices in the chairman statement of the Malaysian companies We used IM as the measure for financial reporting quality (FRQ). Secondary data is utilized that is obtained from the annual report and Thomson Reuters Database. The sample of this study comprises companies listed on the Main Market of Bursa Malaysia in 2017-2018. Interestingly, this research findings identify that AC independence has a significantly negative relationship with the level of IM measured on the basis of qualitative scores (IMSC1) and quantitative scores (IMSC2). The findings of this research supported the agency theory because it argues that strong internal governance monitoring mechanisms improve the FRQ and decrease the IM. AC meeting has a significant positive association with the level of IM based on qualitative scores (IMSC1). This result does not support the argument that increasing number of ACs meetings results in reduced IM and enhanced FRQ. Also, the AC meeting has no relationship with the level of IM in the quantitative scores (IMSC2), whereas IM and AC size has no association with AC financial experts. This result may not support the argument of the agency theory that AC size, meeting and financial experts significantly enhances the FRQ. Findings of the study may enable regulatory bodies and policymakers to devise policies and strategies to improve the credibility of financial statements in Malaysia. Future studies may consider the effect of other AC characteristics, like AC quality, AC members' ownership and AC members' remuneration on IM.
Keywords: 650; impression management; chairman statement; financial reporting quality; audit committee; independence